Mutational Analysis of Sigma-1 Receptor’s Role in Synaptic Stability - Ryskamp, Daniel A.; Zhemkov, Vladimir; Bezprozvanny, Ilya (Frontiers in Neuroscience, 2019)
Sigma-1 receptor (S1R) is an endoplasmic reticulum (ER) resident transmembrane protein. In our previous experiments we demonstrated neuroprotective effects of pridopidine, an agonist of S1R, in cellular and animal models of Huntington’s (HD) and Alzheimer’s (AD) disease. Consistent with previous observations, deletion of endogenous S1R with CRISPR/Cas9 in cultured hippocampal neurons resulted in fewer mushroom-shaped dendritic spines. Overexpression of human S1R restored mushroom spine density to control levels. In contrast, overexpression of S1R with the ∆31-50 deletion (linked to distal hereditary motor neuropathy) or the E102Q mutation (linked to amyotrophic lateral sclerosis) destabilized mushroom spines. Recently a crystal structure of S1R was determined in lipidic cubic phase. In the present study we took an advantage of this structural information and performed docking studies with pridopidine and the S1R structural model. We generated a series of S1R point mutations based on residues predicted to be involved in direct association with pridopidine. We discovered that all ligand binding-site mutants were able to compensate for loss of endogenous S1R. However, most of these mutants were not able to support pridopidine-induced rescue of mushroom spines in presenilin-1 mutant cultures. Our mutational analysis was in agreement with in silico docking based on the published S1R crystal structure, with an exception of R119 residue. Our data also suggests that basal S1R activity is required for mature spine stability, whereas agonist-mediated S1R activity is required for stabilization of mushroom spines in the context of disease-causing mutations